INNER CONFLICT: MATHEMATICAL TRUTH AND STUDENTS’ PERCEPTIONS OF TRUTH - Fauzi Mulyatna; Dhoriva Urwatul Wutsqa; Syukrul Hamdi (Universitas Labuhanbatu, 2026)
Purpose – This study aims to identify the forms of inner conflict potentially experienced by students, as reflected in Teaching Modules and Lesson Plans, and to propose preventive alternatives.Methodology – This study employed a qualitative research approach with a phenomenological orientation through documentation studies of Teaching Modules and Lesson Plans developed by pre-service and in-service Professional Teacher Education students from 13 cities across Indonesia. The participants in this study consisted of documents produced by 63 students enrolled in the Professional Teacher Education (PPG) program. Data analysis employed triangulation techniques, including time triangulation through document analysis covering the period from 2023 to 2025, and source triangulation using Teaching Modules and Lesson Plans produced by both in-service Professional Teacher Education (PPG) participants and pre-service teacher candidates, previously known as PPG Daljab and PPG Prajabatan.Findings – Beyond misconceptions, a broader range of issues can generate inner conflict among students. The findings demonstrate that mathematical conceptual contexts continue to produce conflicting interpretations of truth. Inner conflicts within students may arise from several factors: the misperception of truth caused by inaccurate lexical choices in interpreting mathematical concepts, discrepancies between mathematical results and real-world occurrences, the inappropriate selection of instructional media to explain concepts, inaccuracies in mathematical modeling, and logical fallacies in establishing connections between concrete examples and mathematical contexts.Contribution – This study emphasizes the importance of presenting mathematical truth clearly, unambiguously, and in ways that align with students’ everyday experiences. Furthermore, teachers should avoid generalizing a single mathematical truth across all contexts.